The South China Sea for China, the United States, and what choice for Vietnam - Cường Nguyễn Anh (Cogent Social Sciences)
Although it is not the most significant feature on the strategic map of the United States, it is firmly in favor of the South China Sea, maintaining its status as an area of international waters for the foreseeable future. It will allow for the unimpeded passage of cruise ships and commercial transport vessels. Even though the United States and China are the two actors with the most influence on the political situation in the South China Sea, and even though Vietnam is an indispensable subject in this area, the strategic interests of the United States and China are considered to be crucial for each country. Vietnam is an indispensable subject in this area. Because the South China Sea is so strategically important to China, the United States, and Vietnam, it is likely that these three countries will come into conflict over it shortly. Which political maneuvers and decisions on the part of these two global superpowers affect the current situation in the South China Sea? Moreover, what other options does Vietnam have when it comes to those behaviors?